Traumatic amputations - Clasper, Jon (Br J Pain, 2013)
Traumatic amputations remain one of the most emotionally disturbing wounds of conflict, as demonstrated by their frequent use in films to illustrate the horrors of war. Unfortunately, they remain common injuries, particularly following explosions, and, in addition, many survivors require primary amputation for unsalvageable injuries or to save their life. A third group, late amputations, is being increasingly recognised, often as a result of the sequelae of complex foot injuries. This article will look at the epidemiology of these injuries and their acute management, complications and outcome.